RELEVANSI PENDIDIKAN ISLAM PADA MASA KHULAFAUR RASYIDIN DALAM PEMBENTUKAN KARAKTER GENERASI MUSLIM DI ERA GLOBALISASI - Atika, Siti Nur; Ismatul Mawla; Nurlatifah, Siti; Marwatussofa, Arizcha; Oktaviani , Vera; Faiz Fikri Alfahmi (An-Nahdlah: Jurnal Pendidikan Islam, 2025)
Islamic education during the period of the Khulafaur Rasyidin played a crucial role in shaping a strong and morally upright Muslim generation. This study aims to analyze the relevance of Islamic education during that era in the context of character formation for the Muslim generation in the era of globalization. In this rapidly advancing global era, Islamic education faces significant challenges in preserving religious values and Islamic identity. This research uses a qualitative approach with literature analysis techniques to explore the principles of Islamic education during the Khulafaur Rasyidin period and its relevance to contemporary Islamic education. The findings indicate that fundamental principles such as the teachings of Tawhid, morality, and the integration of worldly and spiritual knowledge from that era are still highly relevant for the formation of Muslim youth's character today. This study concludes that Islamic education during the Khulafaur Rasyidin era can serve as a guide in addressing the challenges of globalization, emphasizing character formation and balanced integration of both worldly and spiritual knowledge, while reinforcing Islamic identity amidst the materialistic global culture.